292 Rest Schemes and Inflight Sleep Duration on Long Range and Ultra-Long Range Commercial Airline Routes. (3rd May 2021) - Rempe, Michael; Rasmussen, Ian; Belenky, Gregory; Lamp, Amanda
Abstract: Introduction: Pilots flying long range (LR; 8-16 hour) and ultra-long range (ULR; 16+ hour on 10% of trips) commercial airline routes use a variety of work/rest schedules during flights, resulting in a wide distribution of total inflight sleep time (TIFS) amounts. Since sleep is a strong predictor of performance, it is important to quantify TIFS and determine rest scheme patterns that optimize sleep opportunity and subsequent alertness and performance. Here we report rest schemes for pilots on LR and ULR routes and longer TIFS values than previously reported. These rest schemes can serve as templates to increase TIFS and improve pilot performance, particularly on ULR routes. Methods: 427 commercial airline pilots provided data for this sub-study that was part of a larger study on Fatigue Risk Management System (FRMS) routes. Inflight sleep timing and duration were measured on 3 LR and 5 ULR routes. Inflight sleep times were self-reported in a sleep/work logbook and verified using actigraphy. Results: Most outbound and inbound landing crews took one break during the second half of the flight (average LR TIFS=4.0 hr; average ULR TIFS=4.9 hr), while most outbound and inbound relief crews consequently took one break during the first half of the flight (average LR TIFS=3.5 hr; average ULR TIFS=4.5 hr). However, three of the five ULR routes used more complex split rest schemes for landing and relief crews, primarily on outbound flights (average TIFS=5.0 hr). Across all routes and both crews, the maximum average TIFS reached ~6 hours. Conclusion: Our results indicate that pilots on average are sleeping inflight more than previous studies demonstrated. Additionally, we found that crews on some ULR flights used more complicated rest schemes, but still generally preferred 2 or 3 breaks. These findings have implications for airline procedures and aviation policies by showing that pilots may be sleeping longer than originally expected on LR and ULR flights. Recommending rest schemes that allow for the greatest inflight sleep opportunity may provide the best chance for inflight recuperation, especially before the Top of Descent critical phase of flight. Support (if any): United Airlines